Invisible travellers: a mini review on the presence and the ecological implications of microplastics in remote areas - Lebepe, Jeffrey; Buthelezi, Nana M. D.; Manganyi, Madira C. (Frontiers in Environmental Science, 2025)
Microplastics (MPs) are becoming a cause for concern in the environment due to their potential to cause adverse effects. Microplastic studies have focused on environments that are in proximity to human activities, with the polar regions, remote wetlands, groundwater, mountain tops, and remote streams, and those draining protected catchments receiving little attention. The review aims to unpack evidence of microplastic occurrence in remote areas, the transport pathways, reasons for limited studies, potential ecological effects, and identify the research gaps, thereof. Microplastics reach remote areas primarily through an atmospheric pathway, whereas flowing rivers and migratory organisms are showing to contribute a considerable amount. Fibres were found to constitute >90% of the morphotypes in remote ecosystems, with particle size below 100 µm being more prominent. Microplastic research in remote areas received little attention due to perceptions that they are not affected by anthropogenic activities. Moreover, inaccessibility and the vague policy posture and implementation are among the reasons hindering microplastic studies in remote areas. Nevertheless, there is a need for microplastic studies in remote areas due to their potential ecological impacts. Effects on the physiology of organisms, nutrient cycling, climate, microbial communities, and sequestration capacity were observed in remote ecosystems. Nevertheless, the morphotype-related impacts and vertical distribution have been poorly studied. Moreover, nothing has been done on the projection and modelling of the cumulative effect of microplastics in remote ecosystems. Given the scale of the problem, international collaborations are also recommended for the sustainable protection of ecosystems and their ecological processes in a global context.